Managing Complexity: The Efficiency of administrative performance and the reemergence of economic planning for the reconciliation of strategic interests of territories - Celati, Benedetta (P.A. Persona e Amministrazione, 2023)
The convergence of multidimensional crises has contributed to change the framework of strategic choices that impact the present and the expected future. The boundaries of climate and environmental action define the new margins of manoeuvre for political and administrative institutions, shaping an institutional system increasingly influenced by the need to provide rapid regulatory responses to emergencies (from pandemics to energy) as well as to the challenges posed by the demographic crisis and economic recession. This scenario requires an administrative decision-making process adapted to the management of a complex reality, in which the role of scientific knowledge and technical skills (particularly the digital technologies) – for its ability to reengineer the administrative machine – are assuming a crucial importance. Hence efficient administrations capable of knowledge and foresight, rather than simply reducing procedural steps, are needed. The efficiency of administrative performance, meant as the suitability of the organisation to best serve its purpose, is therefore fundamental not only to ensure that the administration is able to respond to the needs of the citizen, in the mediation of different interests, but also to legitimise public intervention, in observance of Article 97 of the Italian Constitution. Starting from this assumption, the paper intends to investigate how the fulfilment of the public interest of administrative action – namely the efficiency of public administration – can be declined in the territories, in the form of the principles of adequacy and rationality, i.e. in the construction of the most adequate and effective responses to the needs expressed in the various contexts. Strategic decisions in the energy field (as in the case of the procedures for the installation of regasifiers and floating gas storage terminals) represent in this sense a specific prism of analysis, being the point of fall of simplification logics aimed at the achievement of objectives of national interest as well as of deep conflicts at local level that call into question the issues of ecological democracy and the ability to make the choices made by the administration adequately comprehensible, between security and environmental concerns. In this sense, planning activity is becoming increasingly central, in its triple dimension, now also approved by the European institutions, of economic, environmental and spatial planning at the same time. The protection of the environment, the fight against climate change and the objective of biodiversity, beyond the traditional model of sustainability, seem in fact to provide the foundations, in a perspective of positive territoriality, to realise experiences already attempted in the past of a development-oriented administration, i.e. capable of stimulating the production of value (social, cultural, environmental, economic) from the specific potential resources of a territory.